Monotone Flows with Dense Periodic Orbits (European Journal of Pure and Applied Mathematics, 2019)
The main result is Theorem 1: A flow on a connected open set X âŠ‚ R d is globally periodic provided (i) periodic points are dense in X, and (ii) at all positive times the flow preserves the partial order defined by a closed convex cone that has nonempty interior and contains no straight line. The proof uses the analog for homeomorphisms due to B. Lemmens et al. [27], a classical theorem of D. Montgomery [31, 32], and a sufficient condition for the nonstationary periodic points in a closed order interval to have rationally related periods (Theorem 2).